Partisipasi dalam Program Nasional Pemberdayaan Masyarakat Mandiri Perkotaan Kelurahan Taas Kota Manado - Kalesaran, Ferdinand (JURNAL ILMIAH SOCIETY, 2015)
Participatory development model can be regarded as a form of reaction to management development paradigm or neo-liberalism is closely modeled on the many failures. The purpose of this study was to mengenalisis types of community participation in the National Program for Community Empowerment Taas Urban Village District of Manado city Tikala through the stages of planning and decision-making, implementation, utilization and evaluation of activities.The conclusion of this study is the village community Taas Tikala Manado city districts participate actively in decision-making, implementation, and utilization as well as the maintenance of the results of the activities, but still less involvement in the evaluation. It is recommended that people should take an active part in the evaluation, because at this stage is considered as feedback can provide input for the improvement of the implementation of the program / activity further.Â Keywords: Participation, Community Empowerment